Hearing evaluation after myringoplasty (Bangladesh Journal of Otorhinolaryngology, 2010)
This study was carried out to assess the graft take rate as well as hearing improvement aftermyringoplasty with temporal fascia graft by underlay technique. Study was done in departmentof ENT and Head-Neck Surgery of BSMMU, Dhaka Medical College Hospital and BIRDEM fromJuly 2006 to June 2007. Sixty (60) patients were included prospectively for this work. In thisstudy graft take rate was 85% (51 out of 60) and graft failure was 15% (9 out of 60). The agerange of the patients was 10 to 50 years. Highest number of patients was in the age group of 21to 30 years and graft take was also maximum in this age group. Graft take rate of small sizeperforation (100%) and medium size perforation (93.23%) had more than subtotal perforation(77.77%). Success rate of posterior perforation was maximum (93.75%) followed by anteriorperforation (88.23%). In case of approach of operation postaural approach had maximum successrate (88.09%) followed by endaural (75%) and transcanal approach (80%). In this study themean pre and postoperative air conduction threshold in the successful cases were 34 dB and 24dB respectively, with a mean audiological improvement of 10 dB. Improvement of mean air bonegap was 11 dB. Of the successful cases hearing was improved in 31 patients (60.78%) and 20patients (39.21%) showed no significant hearing improvement. From this study it can be concludedthat myringoplasty is a valid treatment modality for tympanic membrane perforation.Keywords: Myringoplasty; Graft take rate; Hearing improvementDOI: 10.3329/bjo.v16i1.5777Bangladesh J Otorhinolaryngol 2010; 16(1): 23-28